Soil Properties Study for the Western Side of Kut City, Iraq - noor hmood; Mohammed S. Shamkhi (Wasit Journal of Engineering Sciences)
Soil properties checks and classification are an important part of any engineering project as they directly affect buildings as well as agriculture and others. The research aims to create an integrated database for soil properties in the study area, which is the western side of the city of Kut, to know its relationship to groundwater in the region. Laboratory tests were conducted for five soil samples from the Bar Drilling sites to monitor the movement of groundwater in the area. Soil samples were taken when drilling and upon reaching the groundwater level, which was approximately 6 meters sieve analysis, hydrometer, specific gravity, and hydraulic conductivity were also conducted, as well as the content of chlorides and sulfates in the soil was calculated.  For classifying testure of the soil, the triangle of US agriculture department was utilized, soil can be divided into groups by this triangle based on clay, silt and sand proportion.  Results of examination of soil texture  showed that the soil in the first was Clay loam and the second point was Silty Clay loam and in the third point, it was sandy clay loam, while in the fourth point it was silty clay loam and it was in the fifth point silt loam As shown in Table 1. The specific gravity was measured in the field, and the lowest value was 2.65 in the third well, while the highest value was 2.70 in the fifth well. The hydraulic conductivity of the five well points was calculated and was close to each other and considered as an average value of hydraulic conductivity equal to 0.013522. The content of chlorides and sulfates in the soil was calculated due to its importance in knowing the chemical properties. The results showed that the value of the chlorides ranged between (0.154 - 1.72) %, while the values of the sulfate content in the soil ranged between (0.930 - 3.11) %.